Evaluation of Micro RNAs in Aplastic Anemia Patients Presenting at Tertiary Care Hospital LUMHS, Hyderabad - Maleeha Soomro, Sidra Kadir, Noor-Ul-Ain Aziz, Yasir Ahmed Soomro, Rabail Jokio, Ikram Din Ujjan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bone marrow failure that results in pancytopenia causes aplastic anemia clinically. Aim: To determine the frequency of positive microRNAs in plasma of patients with aplastic anemia. Study Design: Descriptive cross-sectional study. Methodology: Aplastic patients were assessed for microRNAs level and patients were considered positive if the level was ≥2 Results: Majority 20(66.7%) of the patients was aged ≤30 years with only 10(33.3%) patients aged above 30 years. There were 22(73.3%) male and 8(26.7%) female patients with a male to female ratio of 2.8:1. Severe, very severe and non-severe aplastic anemia was recorded in 18(60%), 4(13.3%) and 8(26.7%) patients respectively. Taking a cut-off value of ≥27 IU/mL, 15(50%) patients were positive for microRNAs. Conclusion: It was concluded that a substantial proportion of patients with aplastic anemia were positive for microRNAs and the observed frequency increased with increasing severity of disease which suggested potential role of microRNAs in the diagnostic workup and management of aplastic patients. Keywords: Aplastic Anemia and Micro-RNAs.